Direct-write fabrication of solid oxide fuel cells - Kim, Y.-B.; Ahn, S.-J.; Moon, J.; Kim, J.; Lee, H.-W. (Proceedings - Electrochemical Society, 2005)
Line-shaped solid oxide fuel cells (SOFCs) with a multilayered structure have been fabricated using the direct-writing process. Partially stabilized zirconia (PSZ) substrate with sufficient mechanical strength and gas permeability was used as a support for SOFC. The cell comprises the single line-shaped electrode and electrolyte of Ni-YSZ cermet anode, YSZ electrolyte, and LSM cathode. A syringe filled with electrolyte paste and each electrode was loaded into the computer-controlled robo-dispensing machine and the paste dispensed onto a moving plate through a 0.21 mm diameter cylindrical nozzle under a pressure of 0.1 torr. The effective reaction area of fabricated SOFC was 0.03 cm2, and the thicknesses of anode, electrolyte, and cathode were 20 μm, 15 um and 10 μm, respectively. The single line-shaped SOFC fabricated by the directwriting process exhibited OCV of 0.95 V and maximum power density of 0.35W/cm2 at 810°C.